Description of HbA1c Levels in Fatty Liver Disease Patients in a West Jakarta Private Hospital in 2018-2019 - Chandra, Steven Junius; Gunawan, Paskalis Andrew (PT Inovasi Pratama Internasional, 2024)
Fatty liver disease is a chronic disease that is very often found in the community and is often called